Enhancing the implementation of telecommuting (work from home) in Malaysia - Teh, Boon Heng; Soh, Patrick Chin Hooi; Loh, Yin Lee; Ong, Tze San; Hong, Yong Hoe (Canadian Center of Science and Education, 2013)
The telecommuting programme is nothing unusual in developed countries and it is proven benefit regardless of employee or employer perspective. However, this programme has not yet gained popularity in Malaysia. Currently, there are only some forms of telecommute practices and mainly carried out as unofficial agreement between staff and managers and not with the consent of the company administration. Therefore, it is necessary to look into this area particularly initiatives to increase the implementation of telecommuting in Malaysia. Hence, my research will examine in detail the steps and driving factors for telecommuting implementation in Malaysia. The study has revealed two significant driving factors for telecommuting implementation in Malaysia: (1) Job Satisfaction and Commitment and (2) Operating Cost Reduction. Complement with it, a detailed implementation steps for telecommuting have been described in this study, thus providing detailed guidance and reference for any firms who are implementing or planning to implementing a telecommuting programme.